Perilaku Konsumen Remaja Menggunakan Produk Fashion Bermerek Ditinjau dari Kepercayaan Diri - Pranoto, Wahyu; Mahardayani, Iranita Hervi (Jurnal Psikologi: PITUTUR, 2010)
This study aims to empirically examine the relationship  between  consumer  behavior  of teenagers using branded fashion products with confidence.  In  this  study  the  subjects  of research  is  student  in  the  Muria  Kudus University,  with  a  purposive  sampling  based sampling  that  samples  with  characteristics  of teenagers  using  branded  fashion  products. Measuring instrument used to obtain the data is scale  consumer  behavior  teenagers  use fashion branded products and the confidence scale. The  results  obtained  from  both  the correlation  coefficient  rxy  of  0.433  with  p  of 0.000  (p  <0.050),  this  means  there  is  a significant  positive  relationship  on  teenagers consumer  behavior  using  branded  fashion products  with  confidence.  So  the  hypothesis accepted.  Teenangers  consumer  behavior using branded fashion product and confidence gained  on  medium  category.  Effective contribution  to  the  behavior  variable  of consumer confidence at 43.3%.